The Effectiveness of the Psychological Intervention in Amateur Male Marathon Runners - Jaenes, Jose C.; Wilczyńska, Dominika; Alarcón, David; Peñaloza, Rafael; Casado, Arturo; Trujillo, Manuel (Frontiers in Psychology, 2021)
Background: The Marathon runners must have the proper technical preparation to reach excellence and to achieve adequate psychological preparation for the race. Against this background, the current study aims to describe the implementation results of a cognitive-behavioral intervention based on psychological skills training for marathon runners. Methods: Fourteen amateur male marathoners with an average age of 30 (SD = 5.75) were trained with various emotional and cognitive control techniques to enhance their performance in competition. Various psychological variables, related to the subjects level of perceived stress, and to qualitative characteristics of their thoughts were measured before and after the target marathon race. Results were analyzed through non-parametric tests for two related samples. The Cohen’s d effect size for single-group pretest-posttest repeated measures were also performed. Results: Statistical analysis reveals that, controlling for age and running experience, the intervention decreased significantly the level of perceived stress and the occurrence negative thoughts before the race, during, and after the race. Conclusion: Training in cognitive control and relaxation techniques, as part of the psychological skills training could determine the quality of performance of marathon runners.